DNA hydroxymethylation controls cardiomyocyte gene expression in development and hypertrophy - Greco, Carolina M. (Nat Commun, 2016)
Methylation at 5-cytosine (5-mC) is a fundamental epigenetic DNA modification associated recently with cardiac disease. In contrast, the role of 5-hydroxymethylcytosine (5-hmC)—5-mC's oxidation product—in cardiac biology and disease is unknown. Here we assess the hydroxymethylome in embryonic, neonatal, adult and hypertrophic mouse cardiomyocytes, showing that dynamic modulation of hydroxymethylated DNA is associated with specific transcriptional networks during heart development and failure. DNA hydroxymethylation marks the body of highly expressed genes as well as distal regulatory regions with enhanced activity. Moreover, pathological hypertrophy is characterized by a shift towards a neonatal 5-hmC distribution pattern. We also show that the ten-eleven translocation 2 (TET2) enzyme regulates the expression of key cardiac genes, such as Myh7, through 5-hmC deposition on the gene body and at enhancers. Thus, we provide a genome-wide analysis of 5-hmC in the cardiomyocyte and suggest a role for this epigenetic modification in heart development and disease.